Interpellative tautologies: A critique of Hegel's philosophy at the University of Berlin - Turpin, Stephen (University of Ottawa (Canada), 2005)
The study undertakes a critical examination of Hegel's philosophy by constructing a Foucauldian critique of Hegel's use of interpellative techniques (i.e. the call to become subjects of Hegelian Science) that rely on tautological arguments. Salient aspects of Foucault's research on history, governmentality, and subjectivity and power are applied, respectively, to Hegel's teleological metaphysics, his concept of Civil Society, and his notion of the State as freedom. Through this Foucauldian reading, poverty is revealed as an endemic feature of the capitalist economy, while war is demonstrated to be a necessary practice of statecraft. By indicating how the interpellation of individuals into subjective categories forecloses alternative arrangements of economic and political power, the study shows that the Hegelian subject is extremely vulnerable to a logic of domination and oppression. The study then unpacks the truth-effects of Hegel's pedagogical design for the University of Berlin, revealing that his attempt to construct a subject of the modern liberal State is a gesture of violence with dangerous political implications.
Keywords: Philosophy.